2015
DOI: 10.7554/elife.06633
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial hypothalamic neurons control a defensive emotion state

Abstract: Defensive behaviors reflect underlying emotion states, such as fear. The hypothalamus plays a role in such behaviors, but prevailing textbook views depict it as an effector of upstream emotion centers, such as the amygdala, rather than as an emotion center itself. We used optogenetic manipulations to probe the function of a specific hypothalamic cell type that mediates innate defensive responses. These neurons are sufficient to drive multiple defensive actions, and required for defensive behaviors in diverse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
193
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 968 publications
(212 citation statements)
references
References 124 publications
(251 reference statements)
19
193
0
Order By: Relevance
“…These three highly interconnected nuclei are selectively recruited by predator exposure (and not by conspecific threat or pain), receive inputs from sensory circuits detecting predatory cues, and target defense output structures like the PAG (Canteras 2002). Accordingly, inhibition of these nuclei impairs defensive responses to predators while their artificial activation promotes defensive responses in both rodents and primates (Lipp and Hunsperger 1978;Canteras et al 1997;Blanchard et al 2005;Wilent et al 2010;Pavesi et al 2011;Silva et al 2013;Kunwar et al 2015;Wang et al 2015).…”
Section: The Predator Fear Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…These three highly interconnected nuclei are selectively recruited by predator exposure (and not by conspecific threat or pain), receive inputs from sensory circuits detecting predatory cues, and target defense output structures like the PAG (Canteras 2002). Accordingly, inhibition of these nuclei impairs defensive responses to predators while their artificial activation promotes defensive responses in both rodents and primates (Lipp and Hunsperger 1978;Canteras et al 1997;Blanchard et al 2005;Wilent et al 2010;Pavesi et al 2011;Silva et al 2013;Kunwar et al 2015;Wang et al 2015).…”
Section: The Predator Fear Circuitmentioning
confidence: 99%
“…Nevertheless, it is important to note that even if the MHDS plays a central role in integrating predator fear, anti-predator defense can, in some specific cases, rely on alternative circuits bypassing the hypothalamus (Kunwar et al 2015). For instance, rapid responses to looming stimuli seem to rely on more direct inputs to PAG from SC (Zhao et al 2014;Shang et al 2015) and ultrasound-induce defensive responses may rely mainly on circuits centered in the IC .…”
Section: The Predator Fear Circuitmentioning
confidence: 99%
“…While the continuum of defensive behaviors are most easily described in terms of physical distance between predator and prey Blanchard et al 1989), behaviors within each mode increase as shock density increases, up to a point at which the mode of defense changes and the next set of behaviors emerges (Fanselow 1989;Helmstetter and Fanselow 1993). Therefore, responses may actually be controlled by different levels of a single construct (i.e., different levels of imminence), where intensity is read out as different behaviors (Kunwar et al 2015). It should be noted that Predatory Imminence Theory is an example of a more general approach called functional behavior systems, that has been successfully applied to the motivation for food and sex (Domjan 1994;Fanselow 1994;Timberlake 1994;Timberlake and Fanselow 1994).…”
Section: Predatory Imminence Theorymentioning
confidence: 99%
“…Classic lesion and stimulation studies combined with tract tracing have clearly mapped the landscape and identified critical neural hubs for expression of particular behaviours, but more often than not there are multiple behaviours regulated at an individual hub. For instance, the ventromedial nucleus of the hypothalamus is essential for expression of female sexual receptivity [54,55], but also modulates male mating and aggression [56]. In this issue, Bayless and Shah [44] emphasize the power of the mouse model to allow for targeted deletion or stimulation of specific sets of neurons, such as only those expressing the aromatase enzyme or the androgen receptor, and thereby disentangling the role of those specific neurons from their immediate but distinct neighbours.…”
Section: (B) Modular Control Of Behaviour Via Neural Circuitsmentioning
confidence: 99%